Fracture Network Analysis of Metasedimentary Rock in East Coast Terengganu—An Analogue to Fractured Basement in Malay Basin - PC Ooi, SNF Jamaludin, AHA Latif, . (2017)
Oil and gas explorations have now moved to the basement rocks. Basements are rocks with low matrix porosity and permeability; therefore, fractures provide a path for hydrocarbon flow and storage. The research aims to establish an outcrop that could possibly be an analogue to the fractured basement of the Malay Basin and to apply seismic attributes to enhance the seismic images, thereby reducing the uncertainty of interpretation